Biofortified Crops for Combating Hidden Hunger in South Africa: Availability, Acceptability, Micronutrient Retention and Bioavailability - Siwela, Muthulisi (Foods, 2020)
In many poorer parts of the world, biofortification is a strategy that increases the concentration of target nutrients in staple food crops, mainly by genetic manipulation, to alleviate prevalent nutrient deficiencies. We reviewed the (i) prevalence of vitamin A, iron (Fe) and zinc (Zn) deficiencies; (ii) availability of vitamin A, iron and Zn biofortified crops, and their acceptability in South Africa. The incidence of vitamin A and iron deficiency among children below five years old is 43.6% and 11%, respectively, while the risk of Zn deficiency is 45.3% among children aged 1 to 9 years. Despite several strategies being implemented to address the problem, including supplementation and commercial fortification, the prevalence of micronutrient deficiencies is still high. Biofortification has resulted in the large-scale availability of βcarotene-rich orange-fleshed sweet potatoes (OFSP), while provitamin A biofortified maize and Zn and/or iron biofortified common beans are at development stages. Agronomic biofortification is being investigated to enhance yields and concentrations of target nutrients in crops grown in agriculturally marginal environments. The consumer acceptability of OFSP and provitamin A biofortified maize were higher among children compared to adults. Accelerating the development of other biofortified staple crops to increase their availability, especially to the target population groups, is essential. Nutrition education should be integrated with community health programmes to improve the consumption of the biofortified crops, coupled with further research to develop suitable recipes/formulations for biofortified foods.